Spatiotemporal variations of fractional vegetation cover and its response to topography on the Loess Plateau of China from 1995 to 2024 - Fan Fu; Mingwei Zhao; Cancan Yang; Xiaoli Huang; Yan Xu; Yuan Liu; Shaojie Jia (Geomatics, Natural Hazards & Risk)
To elucidate the mechanisms of vegetation dynamics, this study primarily investigates the spatiotemporal variations in fractional vegetation cover (FVC) on the Loess Plateau and its responses to topography. Leveraging the high-resolution and temporal continuity of Landsat imagery, this study utilized the Google Earth Engine (GEE) platform to acquire imagery from 1995 to 2024. The normalized difference vegetation index (NDVI) dataset was synthesized, and FVC was retrieved using the pixel dichotomy model. Methods including linear regression, Sen + MK analysis, coefficient of variation (CV), Hurst exponent, and multiscale geographically weighted regression (MGWR) were employed to examine long-term FVC dynamics and terrain-driven influences. Results show a significant upward FVC trend (0.449%/a, p < 0.01), with 69.74% of the area showing vegetation improvement (p < 0.05) and 54.32% exhibiting large fluctuations. Future predictions indicate spatial heterogeneity, with 52.99% of the area projected to improve. Under categorized conditions, FVC initially decreases and then increases with elevation and topographic position index, while it exhibits a fluctuating upward trend with increasing slope, terrain roughness, and topographic complexity index. FVC responses to terrain factors are significant (p < 0.05), except for aspect (p > 0.05). These findings provide valuable insights for ecological restoration policies by elucidating the spatial heterogeneity of vegetation and the driving mechanisms of topography.